Erratum to Late Paleozoic fusulinids from Sonora, México: Importance for interpretation of depositional settings, biogeography, and paleotectonics - Calvin H. Stevens; Forrest G. Poole; Ricardo Amaya-Martínez (Revista Mexicana de Ciencias Geológicas)
In the above article, the Table 1 has an error in the identification of the locality numbers (column 1). The corrected table is reproduced on the following page and has been attached to the electronic version of the original paper. The authors apologize for this mistake.